DINAMIKA KELOMPOK PEMBUDIDAYA IKAN PADA USAHA BUDIDAYA IKAN NILA (Oreochromis niloticus) DI DESA SEPAKAT KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Sandra Rokhmad Agustine; Helminuddin; Gusti Haqiqiansyah (2339-1324, 2020)
Sepakat Village is a home for Semoga Jaya and Sumber Rezeki Fish Farming Industry Groups. This study was aimed to analyze the dynamics of Tilapia Fish Farming Groups (Pokdakan) in Sepakat Village, Loa Kulu District, Kutai Kartanegara Regency. This research was conducted from March to October, 2019, in Sepakat Village, Loa Kulu District, Kutai Kartanegara Regency. The sampling method used was purposive sampling method to select the groups used as samples. Moreover, census method was also carried out to count the population who are respondents for this study. The number of respondents was 22 people. The data collection technique was done through observation, questionnaire and interview that were then analyzed by using Likert scale to find out the class intervals. The results of this study showed that, from the aspect of group dynamics, the analysis showed relatively high scores with the average of 167.3 (the range of scores obtained was from 138.7 to 177). Therefore, it indicated that the fish farming groupsstudied were relatively dynamic that the groups members showed good cooperation.